Uncovering methods for the prevention of protein aggregation and improvement of product quality in a transient expression system. (25th November 2014) - Estes, Bram; Hsu, Yueh‐Rong; Tam, Lei‐Ting; Sheng, Jackie; Stevens, Jennitte; Haldankar, Raj
<x xml:space="preserve">Abstract</x> Mammalian expression systems are used routinely for the production of recombinant proteins as therapeutic molecules as well as research tools. Transient expression has become increasingly popular in recent years due to its rapid timeline and improvements in expression level. While improvements to transient expression systems have focused mainly on the level of protein expression, the aspect of protein quality has received little attention. The removal of undesirable products, such as aggregation, depends primarily on purification, requiring additional cumbersome steps, which can lead to a lower product yield and longer timelines. In this study, we show that reducing the level of transcription by transfecting at a lower gene dose improves the quality of secreted molecules prone to aggregation. For gene dosing to have this effect, it is critical for the carrier DNA to be an empty vector containing the same elements as the gene containing plasmid. This approach can be used in combination with a temperature shift to hypothermic conditions during production to enhance the effect. The observed improvements not only minimized aggregation levels, but also generated products with overall superior quality, including more homogeneous signal peptide cleavage and N‐linked glycosylation profiles. These techniques have produced a similar improvement in product quality with a variety of other molecules, suggesting that this may be a general approach to enhance product quality from transient expression systems. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 31:258–267, 2015